1973
DOI: 10.1002/macp.1973.021650131
|View full text |Cite
|
Sign up to set email alerts
|

Über den lösungsmitteleffekt bei der silylierung von cellulose mit hexamethyl‐disilazan

Abstract: Nach FINKBEINER und KLEBE 1) ist es moglich, Trimethylsilylcellulose mit Hexamethyl-disilazan in Hexamethyl-phosphoramid darzustellen. Das Reaktionsprodukt ist in einigen apolaren Losungsmitteln loslich.Da Hexamethyl-disilazan ein relativ inaktives Silylierungsmittel ist, hielten wir es von Interesse zu untersuchen, welche Rolle die Losungsmittel bei dieser Silylierungsreaktion spielen, ob sie z. B. eine aktivierende Wirkung auf das Hexamethyl-disilazan ausuben oder ob die Losungsmittel nur die Struktur der Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Finally, we note that the solvent-dependent formation of 1 is consistent with the silylation literature. For example, Nagy et al reported that the silylation of cellulose with HN­(SiMe 3 ) 2 in the presence of a Me 3 SiCl catalyst proceeded smoothly in pyridine, DMSO, and DMF, while no reaction was observed in acetonitrile, nitromethane, and nitrobenzene . Similarly, Zipse et al reported that the silylation of various primary and secondary alcohols with t BuMe 2 SiCl was slow in CHCl 3 and CH 2 Cl 2 but proceeded much faster in DMF .…”
Section: Resultssupporting
confidence: 86%
“…Finally, we note that the solvent-dependent formation of 1 is consistent with the silylation literature. For example, Nagy et al reported that the silylation of cellulose with HN­(SiMe 3 ) 2 in the presence of a Me 3 SiCl catalyst proceeded smoothly in pyridine, DMSO, and DMF, while no reaction was observed in acetonitrile, nitromethane, and nitrobenzene . Similarly, Zipse et al reported that the silylation of various primary and secondary alcohols with t BuMe 2 SiCl was slow in CHCl 3 and CH 2 Cl 2 but proceeded much faster in DMF .…”
Section: Resultssupporting
confidence: 86%
“…One of the main reagents, HMDS, was used to prepare trimethylsilyl cellulose (TMSC) since the 1950s [25]. Various catalysts (mostly acidic, such as HCl) and heating should be used to increase the silylation efficiency of HMDS [26,27]. The silylation reactions of the cellulose fibers of the filter paper with HMDS were summarized in Scheme 2a.…”
Section: Silylation Of Cellulose With Hmdsmentioning
confidence: 99%
“…It was obvious that with the increase of catalyst contents, silylation yield was increased. For the mechanism of TMSCl as catalyst, Nagy et al54 gave an explanation in their work. First, TMSCl with high reaction activity reacted with hydroxyl groups and released HCl as byproduct.…”
Section: Resultsmentioning
confidence: 99%